Hospital-Acquired Urinary Tract Infections in Turkey: A Nationwide Multicenter Point Prevalence Study - Leblebicioglu, H; Esen, S (W B Saunders Co Ltd, 2003)
Hospital-acquired urinary tract infection (UTI) is the most common infection acquired in hospitals. The aim of the study was to determine the prevalence of UTIs in Turkey. A nationwide one day point-prevalence survey was conducted. Centers for Diseases Control and Prevention (CDC) standard definitions for nosocomial UTIs were used. Data were collected by detailed uniform questionnaires for each patient with UTI. A total of 13 269 patients were investigated, the number of patients observed in each hospital varied from 21 to 1329 patients, an average of 458 patients per prevalence study per hospital. The overall prevalence of UTI was 1.7%. Fifty-eight (26.1%) of the patients had sepsis or septic shock. Twenty-five (11.3%) patients had culture-proven bloodstream infection. Over 60% (65.3%) of urinary tract infections were associated with urinary catheters. Overall, 78.4% of UTIs were culture-proven. Escherichia coli (32.4%) was the most common reported pathogen, followed by Klebsiella spp. (17.0%), Candidaspp. (12.8%),Pseudomonas aeruginosa.(11.7%) and enterococci 8.5%. The prevalence of ampicillin-resistant E. coli was 23.9% and accounted for 73.8% of all E. coli isolated from UTI 8.2%, and 24.6% of E. coli were resistant to quinolones and ceftriaxone, respectively. There were no resistance to carbapenems in E. colt but 6.25, 40.6, 59.4% of klebsiella spp. were resistant to carbapenems, quinolones and ceftriaxone, respectively. The results of this first national point-prevalence study offers a reliable measure of the prevalence of nosocomial UTIs at hospitals in Turkey and provides a baseline for future studies which will enable the monitoring of trends over time. C 2003 The Hospital Infection Society
Keywords: Nosocomial Infection; Urinary Tract Infection; Turkey; Point Prevalence Study